Removing Basic Fuchsine Dye by Adsorption over CuCo2O4 Nanocomposite as an Active Adsorbent Surface - Ali A. Kadhim; Muneer A. Al-Da’amy; Salah H. Kadhim; Eman Talib Kareem (مجلة بغداد للعلوم)
This study involves the synthesis of CuCo2O4 spinel-type nanocomposite. This material was synthesized using the co-precipitation method and characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-rays Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Atomic Force Microscopy (AFM). The activity of the synthesized materials was investigated by following removing basic fuchsine (BF) dye from its aqueous solution by adsorption. Different adsorption parameters were conducted involving the dose of adsorbent surface, time of adsorption, pH of the medium, and temperature. The optimum removal efficiency was around 97 % at contact time 5 minutes, 0.005g of dose the surface adsorbent, pH = 8 and 50 mg. L-1 concentration of dye.  Thermodynamic parameters for the adsorption of this dye over the prepared materials were also conducted such as free energy (∆G) negative. While enthalpy (∆H) positive which indicates the adsorption was spontaneous and endothermic, also entropy (∆S) was positive shows the affinity of the adsorbent towards the adsorbate.